Penyelesaian Pembiayaan Murābahah Bermasalah Di PT. BPRS MAM Cabang Kulon Progo Tahun 2018-2020 - Fathudin (Al-Musthofa: Journal of Sharia Economics, 2020)
The Murābahah contract is a contract that is in great demand by Sharia Financial Institutions due to safety factors and minimal risk compared to the Mudhārabah and Musyārakah contracts. However, in its implementation, there is no problematic Murābahah financing, such as Murābahah financing at PT. BPRS MAM (Mitra Amal Mulia) Kulon Progo Branch 2018-2020. This study aims to look at the factors that help problematic Murābahah financing and see from the form / method of solving problematic Murābahah financing at PT. BPRS MAM Kulon Progo Branch. The method used is a qualitative method, namely conducting data interview techniques through interviews, observation and documentation. The results showed that the factors causing the problem were triggered by two factors, namely internal factors and external factors. Meanwhile, in the settlement of problematic Murābahah financing at PT. BPRS MAM Kulon Progo Branch uses several stages of settlement with the last alternative which is achieved through the Religious Court (PA) by executing collateral owned by customers.